PENGUKURAN EFISIENSI BANK PERKREDITAN RAKYAT SYARIAH DI INDONESIA MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS (DEA) DENGAN PENDEKATAN INTERMEDIASI TAHUN 2025 - Nailil Azizah -; Zahra Ramadhani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Islamic Rural Banks (BPRS) play an important role in supporting the development of the Islamic financial industry through their intermediation function of collecting public funds and channeling them into financing activities. As competition in the Islamic banking sector continues to increase, efficiency has become an essential indicator for evaluating the ability of BPRS to utilize available resources optimally. This study aims to measure the efficiency level of Islamic Rural Banks in Indonesia in 2025 using the Data Envelopment Analysis (DEA) method with an intermediation approach. This research employs a quantitative method using secondary data obtained from the Islamic Banking Statistics published by the Financial Services Authority (OJK) in 2025. The units of analysis consist of 22 provinces with active BPRS operations. The input variables include total assets and Third-Party Funds (TPF), while financing is used as the output variable. The analysis applies the DEA CCR model (Constant Return to Scale) with an input-oriented approach. The results reveal that the efficiency performance of BPRS varies across provinces. Of the 22 provinces analyzed, only three provinces, namely Riau Islands, Lampung, and DKI Jakarta, achieved full efficiency with a DEA score of 1.000. Meanwhile, the remaining 19 provinces were found to be below the efficiency frontier, indicating opportunities to improve performance through a more optimal utilization of assets and third-party funds in generating financing. The findings suggest that the effectiveness of the intermediation function plays a more significant role than the size of resources owned in determining the efficiency level of Islamic Rural Banks in Indonesia.